Family care experience in a decentralized social home care context - Hlebec, Valentina (Lex localis, 2017)
This survey analyses the scope and intensity of informal care for the elderly residing in their homes in Slovenia and their determinants: the residing municipality of the care recipient, geographical distance between the informal carer and the care recipient, to the care recipients' and the care givers' individual characteristics. With the increasing private out-of-pocket financial contribution, which is determined by municipality, the scope and intensity of informal care shows a significant increase as shown by regression analysis. Inter-municipal cooperation and the introduction of gradual private financial contribution are proposed as tools for improving accessibility of social home care in Slovenia.
Keywords: Social security system; Socialno varstvo; Home nursing; Nega na domu; Older people; Starostniki; Slovenia; Slovenija